Igual consideração e respeito na integridade e liberdade de expressão: o caso do discurso de ódio - Gomes Júnior, Francisco Tarcísio Rocha (2016)
The objective of this paper is contribute to the debate about freedom of speech through the description of Ronald Dworkin‘s concepts of conter-utilitarian rights and of justifications for freedom of speech. Then, the debate about hate speech will be used as example. Knowing that integrity requires that the citizens should be treated equally and that equal concern and respect is a criteria for the choose of the best conception of equality, these concepts of freedom of speech became clearer. The argument is developed demonstrating that these concepts are best interpreted according with the Rawls‘s critic of the Stuart Mill‘s utilitarianism. The same concepts are used by Dworkin to defend the freedom of speech for haters against Jeremy Waldron‘s arguments. The analysis of the Brazilian case Ellwanger shows that this country is in the tradition defended by Waldron and not the American interpretation realized by Dworkin.